2017
DOI: 10.1097/mcg.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Residual Gastric Volume After Bowel Preparation With Polyethylene Glycol for Elective Colonoscopy

Abstract: PEG bowel preparations increase RGV mildly, but seem to have no clinical significance. These results support the current fasting guidelines for colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
2
11
1
1
Order By: Relevance
“…Recently, Cheng et al found a mean RGV of 28.5 ± 23.2 mL in 330 low‐to‐medium risk patients undergoing a same‐day EGD and colonoscopy using a PEG‐based split‐dose bowel preparation with a runway time of 3.4 ± 1.0 h. The RGV did not differ in patients with 2, 3 and ≥3 h runway time, using a total of 3 L of PEG‐ containing bowel preparation. The mean RGV in 165 patients with a runway time of 2–3 h was 27 ± 19.4 mL . Unlike the later study, our data showed a statistically significant increase in RGV when the runway time was ≤3 h. However, this finding needs to be interpreted with caution as there were only 17 patients in this group and such a magnitude of difference is unlikely to be clinically significant.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Recently, Cheng et al found a mean RGV of 28.5 ± 23.2 mL in 330 low‐to‐medium risk patients undergoing a same‐day EGD and colonoscopy using a PEG‐based split‐dose bowel preparation with a runway time of 3.4 ± 1.0 h. The RGV did not differ in patients with 2, 3 and ≥3 h runway time, using a total of 3 L of PEG‐ containing bowel preparation. The mean RGV in 165 patients with a runway time of 2–3 h was 27 ± 19.4 mL . Unlike the later study, our data showed a statistically significant increase in RGV when the runway time was ≤3 h. However, this finding needs to be interpreted with caution as there were only 17 patients in this group and such a magnitude of difference is unlikely to be clinically significant.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed a mean RGV of 17.7 AE 19.2 mL, with a mean runway time of 5.8 AE 2.0 h, which is similar to that reported in multiple studies (20-25 mL), leading to major society guideline recommendations of a clear liquid intake of 200 mL/h for up to 2 h before the induction of anesthesia. 38 37 Unlike the later study, our data showed a statistically significant increase in RGV when the runway time was ≤3 h. However, this finding needs to be interpreted with caution as there were only 17 patients in this group and such a magnitude of difference is unlikely to be clinically significant.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations